1998
DOI: 10.1021/ja973517s
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Echo Envelope Modulation Spectroscopy Reveals and Distinguishes Equatorial and Axial Nitrogen Ligands Bound to VO2+

Abstract: ESEEM (electron spin echo envelope modulation) spectra of a series of vanadyl complexes have for the first time revealed the spectral features that arise from amine nitrogen donors trans to the vanadyl oxo moiety. The complexes [VO(H2O)ada] (1) and [VO(H2O)Hheida] (2) (H2ada, N-(2-acetamido)iminodiacetic acid; H3heida, N-(2-hydroxyethyl)iminodiacetic acid) have recently been synthesized and crystallographically characterized (Hamstra, B. J.; Houseman, A. L. P.; Colpas, G. J.; Kampf, J. W.; LoBrutto, R.; Frasch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 23 publications
(62 reference statements)
4
36
0
Order By: Relevance
“…In agreement with the experiments, all the functionals predict a small value of A N iso and A N z for an axially coordinated nitrogen, like the amino nitrogen in cis-[VO(Hhida) (H 2 O)] [74], but BHandH gives the best results. For this reason, the latter functional is preferred to the others in the application to the models of vanadium proteins.…”
Section: Validation Of the Dft Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with the experiments, all the functionals predict a small value of A N iso and A N z for an axially coordinated nitrogen, like the amino nitrogen in cis-[VO(Hhida) (H 2 O)] [74], but BHandH gives the best results. For this reason, the latter functional is preferred to the others in the application to the models of vanadium proteins.…”
Section: Validation Of the Dft Methodssupporting
confidence: 82%
“…Information on this superhyperfine coupling can be provided by ESEEM spectroscopy, a variant of EPR spectroscopy [62,[69][70][71]. The superhyperfine coupling constants reported for 14 N are in the range 1-8 MHz and vary with the nature, position, and orientation of the ligands [72][73][74]. In studies on the identification of nitrogen donors bound to vanadium in VO 2?…”
Section: Validation Of the Dft Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent inhibitory effect of VO 2ϩ can be abolished by substitution of NH 4 ϩ for K ϩ in the reaction mixture whereas the reaction in the presence of Mg 2ϩ or Mn 2ϩ is not influenced by addition of NH 4 ϩ . Because VO 2ϩ can be coordinated by amines and other nitrogen-donor ligands 3 (41)(42)(43), the high concentration of NH 4 ϩ is likely to cause coordination to VO 2ϩ , converting the system to be equivalent to that in the absence of added divalent metal ion. 4 Table II compares the results of our studies showing the influence of divalent metal ions under single turnover conditions for both intrinsic GTPase and kirromycin-stimulated GTPase activity in the absence of programmed ribosomes.…”
Section: Role Of Mg 2ϩ In Ef-tu Actionmentioning
confidence: 99%
“…It has been demonstrated that ESEEM results not only show the presence or absence of nitrogen nuclei coordinated to vanadyl (and possibly the number of the coordinating nitrogen atoms) but also makes it possible to distinguish different types of nitrogen donors based on the empirical correlation between the type of the nitrogen and the 14 N-hyperfine coupling parameters. 28 The application of the ESEEM technique, for example, to vanadyl complexes with ligands, such as hydroxamic acids, 45 N-(2-hydroxyethyl)iminodiacetic acid, 46 4-[2-(salicylidenamino)ethyl]imidazole, 47 N-{2-[(2-pyridylmethylene)amino]phenyl}pyridine-2-carboxamide (Hccapca), 48 and 1,2-bis(2-hydroxybenzamido)benzene (H 4 hybeb) 49 is well documented.…”
Section: Solution Chemistry Of Vanadium and Zinc Complexesmentioning
confidence: 99%